Multifaceted Roles of Chemokine C-X-C Motif Ligand 7 in Inflammatory Diseases and Cancer - Wu, Qianmiao; Tu, Huaijun; Li, Jian (Frontiers in Pharmacology, 2022)
Over recent years, C-X-C motif ligand 7 (CXCL7) has received widespread attention as a chemokine involved in inflammatory responses. Abnormal production of the chemokine CXCL7 has been found in many inflammatory diseases; nevertheless, the exact role of CXCL7 in the pathogenesis of inflammatory diseases is not fully understood. Persistent infection or chronic inflammation can induce tumorigenesis and progression. Previous studies have shown that the pro-inflammatory chemokine CXCL7 is also expressed in a variety of malignant tumor cells and that CXCL7 binding to its cognate receptors C-X-C chemokine receptor 1 (CXCR1) and C-X-C chemokine receptor 2 (CXCR2) can affect the tumor biological behavior (proliferation, invasion, metastasis, and tumor angiogenesis) in an autocrine and paracrine manner. CXCL7 and its receptor CXCR1/CXCR2, which are aberrantly expressed in tumors, have the potential to become new targets for clinical tumor immunotherapy.